AP‐2 reduces amyloidogenesis by promoting BACE1 trafficking and degradation in neurons. (23rd April 2020) - Bera, Sujoy; Camblor‐Perujo, Santiago; Calleja Barca, Elena; Negrete‐Hurtado, Albert; Racho, Julia; De Bruyckere, Elodie; Wittich, Christoph; Ellrich, Nina; Martins, Soraia; Adjaye, James; Kononenko, Natalia L.
Abstract: Cleavage of amyloid precursor protein (APP) by BACE‐1 (β‐site APP cleaving enzyme 1) is the rate‐limiting step in amyloid‐β (Aβ) production and a neuropathological hallmark of Alzheimer's disease (AD). Despite decades of research, mechanisms of amyloidogenic APP processing remain highly controversial. Here, we show that in neurons, APP processing and Aβ production are controlled by the protein complex‐2 (AP‐2), an endocytic adaptor known to be required for APP endocytosis. Now, we find that AP‐2 prevents amyloidogenesis by additionally functioning downstream of BACE1 endocytosis, regulating BACE1 endosomal trafficking and its delivery to lysosomes. AP‐2 is decreased in iPSC‐derived neurons from patients with late‐onset AD, while conditional AP‐2 knockout (KO) mice exhibit increased Aβ production, resulting from accumulation of BACE1 within late endosomes and autophagosomes. Deletion of BACE1 decreases amyloidogenesis and mitigates synapse loss in neurons lacking AP‐2. Taken together, these data suggest a mechanism for BACE1 intracellular trafficking and degradation via an endocytosis‐independent function of AP‐2 and reveal a novel role for endocytic proteins in AD. Synopsis: BACE1 promotes A production and is a neuropathological hallmark of Alzheimer's disease. This study shows that the endocytic adaptor protein complex‐2 promotes trafficking and degradation of BACE1 in neurons and reduces amyloidogenesis. BACE1 proteins levels are increased in AP‐2 deficient brains. AP‐2 functions downstream of BACE1 endocytosis and promotes BACE1 trafficking en route to lysosomes. Neurodegeneration in AP‐2 KO mice can be rescued by BACE1 haploinsufficiency. Abstract : BACE1 promotes A production and is a neuropathological hallmark of Alzheimer's disease. This study shows that the endocytic adaptor protein complex‐2 promotes trafficking and degradation of BACE1 in neurons and reduces amyloidogenesis.